2020
DOI: 10.1103/physrevb.101.035146
|View full text |Cite
|
Sign up to set email alerts
|

Proximity coupling of superconducting nanograins with fractal distributions

Abstract: We explore the electrical and magnetic properties of a fractal assembly of Josephson junctions with transparent interfaces. For this purpose, we employ an Mg/MgO/MgB 2 nanocomposite with ∼16 vol. % of MgB 2 nanograins, which are distributed in a fractal manner in the normal matrix. Irrespective of the low volume fraction of MgB 2 nanograins, the nanocomposite behaves as a bulk-like superconductor, i.e., zero resistivity, perfect diamagnetism, and strong vortex pinning. Thus, a global Josephson phase coherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In this way, scale invariant textures have been observed in lattice, spin, and charge degrees of freedom in strongly correlated oxide perovskites [16][17][18][19][20][21] and at metal-insulator transitions [22]. These results have shown that scale invariance [23,24] in granular matter near a critical point has been favoring quantum coherence in high-temperature superconductivity [25][26][27][28][29]. Lattice complexity beyond the average crystalline structure effects in the mechanism of high Tc superconductivity at optimum doping is attracting high interest.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, scale invariant textures have been observed in lattice, spin, and charge degrees of freedom in strongly correlated oxide perovskites [16][17][18][19][20][21] and at metal-insulator transitions [22]. These results have shown that scale invariance [23,24] in granular matter near a critical point has been favoring quantum coherence in high-temperature superconductivity [25][26][27][28][29]. Lattice complexity beyond the average crystalline structure effects in the mechanism of high Tc superconductivity at optimum doping is attracting high interest.…”
Section: Introductionmentioning
confidence: 99%